Faith Fleur / Lydia Loney Kanyan - Kanyan, Lydia Loney (2022)
Faith Fleur is an online business to sell hair care product for our customer at all genders and age. The meaning of Faith is loyalty and Fleur is in French words that mean flower so whenever customer wear Faith Fleur hair care product their hair will smell like a flower. The purpose of this business to help people to overcome their problem such as messy hair, hair loss and hair dandruff. In a nutshell, we can conclude that Faith Fleur is business that sell hair care product and can be use by all people including babies. Faith Fleur is a manufacturer of hair care products consisting of Shampoo, Conditioner, Serum, Tonic, Hair Mask, Leaf Vitamin, Hair Mist and so on. This is the reason why this product to be more widespread and high sales as this product can solve hair problems by diversifying the products.